Diversity and Seasonal Ginkgolide variation in Old and Young Trees of Ginkgo biloba - Paul, Shilpi; Bisht, Monisha; Singh, Gopal; Yadav, Shivani (Indian Forester, 2020)
The Ginkgo biloba L. often referred as a living fossil and being the only living member of the Ginkgo family (Ginkgoaceae), only few old established trees and their cuttings are growing in India. It has huge demand in the Global market for various medicinal products. In view of its conservation management and market demand an attempt has been made to analyze the old trees grows in western Himalaya of HR and their comparison with newly seed raised plants at the chemical and molecular levels. Leaf samples of 10 young trees (seed raised; age about 3 years) and 7 old trees (age 35-150 years) were taken for phenotypic and molecular analyses. Protein profile showed segregating band of size 19 kDA in new trees and the old tree of Rajbhawan showed a specific 20 kDA protein band. In AFLP analysis, 958 loci were observed, ofwhich 449 were polymorphic revealing 47.46% polymorphism in overall genotypes. Cluster analyses indicated that all the seed raised new trees were in one group while the old established trees were in another group. Seasonal variation in ginkgolide content was observed in the samples collected at different times (April, June, and October) during the year to complete the cycle and optimize the harvesting time of active principle. The HPLC analysis showed highest levels of ginkgolide A (1.5% DW) and B (0.19% dry wt. basis) in samples collected during the month of June. Ginkgolide A (GBA) ranged from 0.3-1.5 % (dry wt. basis), while ginkgolide B (GBB) ranged between 0.106-0.19 % (dry wt. basis) throughout the season. The results of the study will be presented and discussed in the light of developing strategies for harvesting leaf samples for ginkgolides, developing conservation, and management strategies and introducing new seed raised plants for maintaining genetic diversity.